Origen y domesticación de Tara spinosa (Leguminosae, Caesalpinioideae) - Villena-Velásquez, J.J. (2021)
The "tara" or "taya" (Tara spinosa) is an economically important plant in Peru and other Andean countries, mainly exploited in its wild from. However, no information is known about its origin dispersal and state of domestication, as a basis for understanding the changes arising from its intensive cropping with improved technology and for its conservation. This article, based on biological, archaeological, linguistic and historical sources and field observations, aspects clarifieds, for the first time. It also discusses the direction of selection pressures, the research approach and pending studies. It is tentatively concluded that the domestication centre is located on the Peruvian coast, where the human-"tara" relationship dates back 5100 years. The Tara spinosa has not yet reached the level of a highly domesticated plant and it is possible to find it, not only in its wild state but also in four other intermediate states. Studies are suggested for a better understanding of germplasm variability focusing on the useful parts, components and active principles.